THE EVOLUTION OF COLONIAL LEGACY AND SOCIAL STATUS OF WOMEN, A CASE STUDY OF EGYPT BETWEEN 1952-2016: Received: 13th August 2021; Revised: 27th November 2021, 10th December 2021; Accepted: 14th December 2021 - Gordon, Ruth Frimpomaa Anarfi; Zhang, Qianhong (PEOPLE: International Journal of Social Sciences, 2021)
The topic of female’s rights and gender equality is an issue of the Arab uprisings call for democracy. In the Arab Muslim-majority nations, some creeds have influenced the impact of the gender discussion. Namely Islamic teaching and local cultural practices about females’ duties in a culture in the Arab world: Western, European colonial perceptions of the rights of females, as well as ultimately policy reforms that are gender-related nationwide. The study aims to look at the situations (gender inequality) of women 11. in the Arab world before and after colonization, with a focus on Egypt. The impact of colonial heritage on women’s formal and higher education as well as recent gender practices in the public sphere, the responses from the global actions taken, and response from the national level regarding females’ rights. This research used the descriptive approach relying on literature from publications, presented papers, journals, books, and useful websites to focus on the topic. It also examines the parallels and variations in gender parity reform strategies in Egypt. However, part of the findings is that women’s abilities have been deliberately relinquished to the back and downplayed by society.